An Analysis of Safety and Adverse Events Following Cochlear Implantation in Children Under 12 Months of Age. Issue 10 (December 2017) - Kim, Yesul; Patel, Vijay A.; Isildak, Huseyin; Carr, Michele M.
Abstract : Objective: To determine perioperative morbidity of children ⩽12 months undergoing cochlear implantation (CI). Study Design: Retrospective analysis using the American College of Surgeons National Surgical Quality Improvement Program Pediatric Database (ACS-NSQIP-P). Setting: General acute care children's hospitals, children's hospitals within larger hospitals, specialty children's hospitals, and general acute care hospitals with a pediatric wing. Patients: Children who underwent CI were queried using the ACS-NSQIP-P from 2012 to 2015. Intervention: Cochlear implantation. Main Outcome Measures: Risk factors analyzed include age, prematurity, and presence of congenital disorders. Outcomes analyzed include operative time, length of stay, general surgical complications, readmissions, and related reoperations. Results: Over the database accrual period, the percentage of children ⩽12 months at the time of surgery increased from 2012 to 2015 (6.08–7.78%, p = 0.0752). Total operative time, length of stay (≥1 d), and readmissions for those ⩽12 months were significantly greater compared with those >12 months at the time of surgery ( p < 0.001, p = 0.0037, and p < 0.0001, respectively). There were no statistically significant differences in general surgical complications (i.e., superficial incisional surgical site infections, organ/space surgical site infections, and/or unplanned reoperations) in cases ⩽12 months. Complications specific to CI such as facial nerve paralysis, cerebrospinal fluid leak, and mastoiditis were not recorded in the ACS-NSQIP-P. Conclusion: Infants had no more general surgical complications in the immediate postoperative period compared with older children, although total operative time, length of stay, and readmissions were found to be significantly greater in frequency.